2004
DOI: 10.1249/01.mss.0000106173.81966.90
|View full text |Cite
|
Sign up to set email alerts
|

Regular Exercise as an Effective Approach in Antihypertensive Therapy

Abstract: The data demonstrate that long-term aerobic exercise is associated with a decrease in BP at rest and during exercise, which is comparable to that of drug therapies. This antihypertensive effect of regular training can be maintained as long as 3 yr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 23 publications
2
26
1
5
Order By: Relevance
“…It is well documented that multiple bouts of moderate-tovigorous intensity exercise can result in chronic favourable adaptations in those with elevated BP [13,14]. As early as 1898, Leonard Hill of the London Hospital Medical College published the results of a man who ran 400 yards as fast as possible and recorded a 10−15 mmHg reduction in resting BP 10 min after the run [15].…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that multiple bouts of moderate-tovigorous intensity exercise can result in chronic favourable adaptations in those with elevated BP [13,14]. As early as 1898, Leonard Hill of the London Hospital Medical College published the results of a man who ran 400 yards as fast as possible and recorded a 10−15 mmHg reduction in resting BP 10 min after the run [15].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, current public health guidelines for the prevention of dyslipidaemia recommend physical exercise of moderate intensity [17]. In addition, effects of aerobic exercise on serum lipid levels in individuals with hypertension have been well-reported in the literature [18][19][20][21]. However, only a few studies on the effects of aerobic exercise on serum lipid levels reported the use of antihypertensive drugs by the participants [14,22].…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity is commonly regarded as beneficial to both physical and psychological health, and is seen as an effective preventive measure and treatment for stress-related diseases (Perkins et al, 1986;Ross and Hayes, 1988;Steptoe et al, 1993;Blumenthal et al, 1999;Babyak et al, 2000;Talbot et al, 2002;Ketelhut et al, 2004;Barlow et al, 2006;Nabkasorn et al, 2006). Physically active people show reduced reactivity to physical stressors as well as reduced susceptibility to the adverse influences of life stress (Tucker et al, 1986;Luger et al, 1987;Deuster et al, 1989;Steptoe et al, 1989;Dishman, 1997;Throne et al, 2000;Dishman et al, 2006;Rimmele et al, 2007).…”
Section: Introductionmentioning
confidence: 99%